1980
DOI: 10.1002/cne.901900205
|View full text |Cite
|
Sign up to set email alerts
|

The nucleus of the solitary tract in the monkey: Projections to the thalamus and brain stem nuclei

Abstract: The projections of the nucleus of the solitary tract (NST) were studied by autoradiographic anterograde fiber-tracing and horseradish peroxidase (HRP) retrograde cell-labeling. Tritiated proline and leucine were deposited in electrophysiologically identified regions of NST. Injections of NST at levels caudal to where the vagus enters the nucleus, from which responses were evoked by stimulation of cranial nerves IX and X, revealed topographically organized bilateral projections to, most prominently, the ventrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
180
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 411 publications
(185 citation statements)
references
References 50 publications
4
180
1
Order By: Relevance
“…In the suncus, as in other mammals, the Pb is the major target for projections from the NTS, and has generally been regarded as a relay of visceral and gustatory afferents to higher levels (Norgren and Leonard, 1973;Sakai et al, 1977;Norgren, 1978;Ricardo and Koh, 1978;Beckstead et al, 1980;King, 1980;Herbert et al, 1990). Physiological studies have suggested that taste-responsive neurons are primarily located in the MPb and that viscerosensory-responsive neurons are located in the LPb (Norgren and Pfaffmann, 1975;Hermann and Rogers, 1985;Ward, 1989;Halsell and Frank, 1991).…”
Section: Projections From the Ntsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the suncus, as in other mammals, the Pb is the major target for projections from the NTS, and has generally been regarded as a relay of visceral and gustatory afferents to higher levels (Norgren and Leonard, 1973;Sakai et al, 1977;Norgren, 1978;Ricardo and Koh, 1978;Beckstead et al, 1980;King, 1980;Herbert et al, 1990). Physiological studies have suggested that taste-responsive neurons are primarily located in the MPb and that viscerosensory-responsive neurons are located in the LPb (Norgren and Pfaffmann, 1975;Hermann and Rogers, 1985;Ward, 1989;Halsell and Frank, 1991).…”
Section: Projections From the Ntsmentioning
confidence: 99%
“…Based on neurological studies showing that the NTS controls the gastrointestinal tract via the dorsal motor nucleus of the vagus (DMV) (Morest, 1967;Cottle and Calaresu, 1975;Norgren, 1978;Beckstead et aL, 1980;Rogers et aL, 1980;Arends et al , 1988), and controls the pharynx, larynx, and esophagus via the nucleus ambiguus (Amb) (Morest, 1967;Cottle and Calaresu, 1975 Cunningham et al, 1991), the NTS appears to play an important role as the afferent system of all visceromotor reflexes, including the emetic response. Nevertheless, to define the neural pathways involved in the vomiting reflex, further comparative studies are necessary, especially in species having vomiting peculiarities.…”
mentioning
confidence: 99%
“…Then, gustatory information in the VPMpc is transferred to the granular IC [51,52] which projects to the lateral and basal nuclei of the amygdala [53] and the orbitofrontal cortex (OFC) where visual and olfactory modalities converge with taste and oral texture [51,52,[54][55][56]. In the rodent, the taste part of the NTS projects to the PBN [57] which projects to the VPMpc, the central nucleus of the amygdala (CEA), and to the hypothalamus [58,59] (Fig. 2), and the PBN has reciprocal connections from the CEA and hypothalamus [60,61].…”
Section: Pathways Of Oral and Visceral Information Neural Pathwaysmentioning
confidence: 99%
“…3), the visceral region in the caudal part of the NTS projects to the PBN. The PBN projects to the rostral half of the VPMpc (the non-taste part), the CEA, the lateral hypothalamic nuclei, the VTA, and to the SN in macaques [52,57,62,63]. The visceral part of VPMpc projects to the agranular insula which is located just posterior to the OFC [64,65] and the insula projects to the ventral striatum (VS) [66].…”
Section: Pathways Of Oral and Visceral Information Neural Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation